The attention economy : understanding the new currency of business - Davenport, Thomas H. 1954-; Beck, John C. (Boston : Harvard Business School Press, 2001)
"This book argues that today's businesses are headed for disaster - unless they can overcome the dangerously high attention deficits that threaten to cripple today's workplace. Accenture consultants and academics Thomas Davenport and John Beck explain that the problems for business people lie on both sides of the attention equation: on getting and holding the attention of information-flooded employees, consumers, and stockholders, and on parceling out their own attention in the face of overwhelming options.
The resolution: learn to manage this critical yet finite resource, or fail.".
"Drawing from compelling research, the authors outline four perspectives on attention management that are critical to understanding its impact on business: (1) measuring and allocating attention, (2) understanding and leveraging its psychological dimensions, (3) mastering new streamlining technologies, and (4) adapting lessons from traditional attention industries like advertising.
Using these perspectives, the authors shine new light on critical business areas including e-commerce, organizational leadership, information and knowledge management, and strategy. Attention management can be applied to help companies improve talent motivation and retention, avoid employee burnout, win customer loyalty on the Web, more effectively sell products and services, impress investors and analysts, and more."--BOOK JACKET.
1. A New Perspective on Business: Welcome to the Attention Economy -- 2. Attention, the Story so Far: What Attention Is and Isn't -- 3. Doing a Number on You: The Measurement of Attention -- 4. From Amoebas to Apes: The Psychobiology of Attention -- 5. Luddites Beware: Attention Technologies -- 6. The Hidden Persuaders: Lessons from the Attention Industries -- 7. Eyeballs and Cyber Malls: E-Commerce and Attention -- 8. Command Performance: Leadership and Attention -- 9. Focused Choices and Global Resources: Strategy and Attention -- 10. Off the Org Chart: Organizational Structure and Attention -- 11. "You've Got (Lots and Lots of) Mail": Managing Information, Knowledge, and Attention -- 12. From Myopia to Utopia: The Future of the Attention Economy.
Includes bibliographical references and index.
Keywords: Personal information management; Attention